EFEKTIFITAS PENAMBAHAN RAGI DAN PUPUK TERHADAP KADAR ALKOHOL BIOETANOL DENGAN BAHAN BAKU JAMBU CITRA - Hastuti, Endah Dwi; Prihastanti, Erma (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
Improvement of bioethanol production using various raw materials had been developed. Jambu citra is one of the raw materials abundantly available. Least of infornation concering the production treatment to provide qualified bioethanol product becomes the problem in optimizing thee productivity of bioethanol. This research aimed to study the alcohol concentration produced from bioethanol production using jambi citra wastes and to study the optimum composition of yeast and fertilizer to produce bioethanol with good alcohol concentration. This research was conducted through experiment including treatment of congrol (without yeast and fertilizer), 1R1P (45 gr yeast + 45 gr fertilizer), 2R1P (90 gr yeast + 45 gr fertilizer), 1R2P (45 gr yeast + 90 gr fertilizer), dan 2R2P (90 gr yeast + 90 gr fertilizer) for each 100 gr of jambu citra samples and 3 days of fermentation period. The result showed that alcohol concentration of each treatment was 2,2% (control); 5,3% (1R1P); 6,7% (2R1P); 5,3% (1R2P); dan 4,0% (2R2P). To extract bioethanol resulted from the fermentation process, the extraction periods required for each treatment was 80.3 minutes; 71.3 minutes; 70.7 minutes; 62.0 minutes and 85.0 minutes for treatment control, 1R1P, 2R1P, 1R2P dan 2R2P respectively. The volume of alcohol resulted from each treatments was 5.0 ml; 11.7 ml; 7.8 ml; 11.6 ml dan 8.5 ml. The combination of yeast and fertilizer required to optimize the production of bioethanol from 100 gr of jambu citra wastes was by adding 45 gr of yeast and 90 gr of fertilizer. Keywords: bioethanol, jambu citra, yeast, fertilizer